Nurturing gut-brain research: an interview with Helen Vuong on the maternal microbiome in neurodevelopment (Nature Portfolio, 2021)
Helen Vuong is a postdoctoral fellow in the Hsiao lab at the University of California, Los Angeles, where she is currently funded by a K99 Pathway to Independence Award from the National Institutes of Health. In this Q&A, Dr. Vuong tells us about her current work and the importance of tailoring scientific educational experiences to students. Dr. Vuong also shares tips on how to better support young parents in STEM.